Numerical performance assessment of a new wave energy conversion system (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The greater wave energy content in deeper waters has initiated substantial research in offshore wave energy converters (WECs). However, the existing WECs are hindered by their high initial costs, primarily attributed to the demanding mechanical workloads they endure. This paper describes a novel wave energy conversion system developed at IST for deep waters (around 20-50 meters) based on a floater and a ballast, suspended by a set of cables. In the novel approach, the WEC is made up essentially by membranes, without a rigid structure, thus reducing the initial cost of investment comparing to other solutions.A simplified numerical model in the time-domain of the system based on linear theory is developed and a preliminary performance assessment under regular and irregular wave conditions (for conditions prevalent along the western coast of Portugal) is performed. Additionally, the effect of the ballast mass is considered. The results reveal the system's non-linear behavior during the floater's ascending phase and emphasize the significant influence of the ballast's mass on power production.